Design Based Research: the Way of Developing and Implementing Educational Innovation - Štemberger, Tina; Cencič, Majda (World journal on educational technology, 2016)
Abstract The appropriate implementation of innovation is a crucial factor in improving educational practice. In the implementation process, there is, however, often a lack of interaction between designers and practitioners that would enable the latter to become competent enough to implement theoretical knowledge into practice and to have an ongoing support from designers. Design-based research is based on close cooperation between researchers, practitioners and designers which consequently allows greater integration of research and practice in education. In the present paper, the beginnings, development, basic characteristics, advantages, disadvantages and the research process of design-based research are reviewed and an example of design-based research is presented.